Thermoelectric Transport Properties of Cu Nanoprecipitates Embedded Bi2Te2.7Se0.3. (24th March 2015) - Lee, Eunsil; Kim, Jin Il; Choi, Soon-Mok; Lim, Young Soo; Seo, Won-Seon; Kim, Jong-Young; Lee, Kyu Hyoung
Abstract : We suggest a simple and scalable synthesis to prepare Cu-Bi 2 Te 2.7 Se 0.3 (Cu-BTS) nanocomposites. By precipitating Cu nanoparticle (NP) in colloidal suspension of as-exfoliated BTS, homogeneous mixtures of Cu NP and BTS nanosheet were readily achieved, and then the sintered nanocomposites were fabricated by spark plasma sintering technique using the mixed powder as a raw material. The precipitated Cu NPs in the BTS matrix effectively generated nanograin (BTS) and heterointerface (Cu/BTS) structures. The maximumZ T of 0.90 at 400 K, which is 15% higher compared to that of pristine BTS, was obtained in 3 vol% Cu-BTS nanocomposite. The enhancement ofZ T resulted from improved power factor by carrier filtering effect due to the Cu nanoprecipitates in the BTS matrix.